Efektivitas Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Sekolah - Ragilia Mei Cahyati; Amini; Mhd. Isman (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
The purpose of this study was to determine: The effectiveness of the principal's leadership in improving school quality at SMA Muhammadiyah 1 Medan. This research uses a mixed method approach, with the research design being the exploratory sequential. The data collection techniques used are observation, interviews, documentation, and questionnaires. Qualitative data analysis techniques in this case use data reduction, data presentation, conclusion drawing. As for quantitative data analysis techniques in this study, namely using simple linear regression tests. The results of this study indicate that the leadership of the principal of SMA Muhammadiyah 1 Medan is effective in improving school quality with a leadership style that is lived, namely participatory-transformational. Principals improve the quality of schools can be influenced and there is a relationship with indicators of teacher performance whose influence is 15.5%, the school organizational climate is 27.5%, students enter college 26%, student achievements are 31%, and the graduation of students in taking the National Exam 100% pass.